Power systems analysis - Murty, P. S. R. (Butterworth-Heinemann, 2017)
Power Systems Analysis, Second Edition, describes the operation of the interconnected power system under steady state conditions and under dynamic operating conditions during disturbances. Written at a foundational level, including numerous worked examples of concepts discussed in the text, it provides an understanding of how to keep power flowing through an interconnected grid. The second edition adds more information on power system stability, excitation system, and small disturbance analysis, as well as discussions related to grid integration of renewable power sources. The book is designed to be used as reference, review, or self-study for practitioners and consultants, or for students from related engineering disciplines that need to learn more about power systems.--Provided by publisher.